The Drosophila orthologue of the INT6 onco-protein regulates mitotic microtubule growth and kinetochore structure. - Fioranna Renda (PLoS Genetics, 2017)
INT6/eIF3e is a highly conserved component of the translation initiation complex that interacts with both the 26S proteasome and the COP9 signalosome, two complexes implicated in ubiquitin-mediated protein degradation. The INT6 gene was originally identified as the insertion site of the mouse mammary tumor virus (MMTV), and later shown to be involved in human tumorigenesis. Here we show that depletion of the Drosophila orthologue of INT6 (Int6) results in short mitotic spindles and deformed centromeres and kinetochores with low intra-kinetochore distance. Poleward flux of microtubule subunits during metaphase is reduced, although fluorescence recovery after photobleaching (FRAP) demonstrates that microtubules remain dynamic both near the kinetochores and at spindle poles. Mitotic progression is delayed during metaphase due to the activity of the spindle assembly checkpoint (SAC). Interestingly, a deubiquitinated form of the kinesin Klp67A (a putative orthologue of human Kif18A) accumulates near the kinetochores in Int6-depleted cells. Consistent with this finding, Klp67A overexpression mimics the Int6 RNAi phenotype. Furthermore, simultaneous depletion of Int6 and Klp67A results in a phenotype identical to RNAi of just Klp67A, which indicates that Klp67A deficiency is epistatic over Int6 deficiency. We propose that Int6-mediated ubiquitination is required to control the activity of Klp67A. In the absence of this control, excess of Klp67A at the kinetochore suppresses microtubule plus-end polymerization, which in turn results in reduced microtubule flux, spindle shortening, and centromere/kinetochore deformation.